2020
DOI: 10.15575/jpba.v4i1.8221
|View full text |Cite
|
Sign up to set email alerts
|

Technology for Four Skills Arabic in the Era Emergency of Covid-19 in Indonesia

Abstract: The integration of technology and learning has become the primary key in developing various Arabic learning models in emergencies of the COVID-19 era. This study aims to describe and uncover the impact of technology on the learning process of Arabic on four Arabic language skills. This research uses a qualitative approach design utilizing the case study research method. Data obtained through observation techniques, interviews, and documentation with data analysis techniques using the theory of Milles and Huber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
0
16
0
4
Order By: Relevance
“…The Covid-19 pandemic that has attacked the world recently has had a profound impact on all lines of life, especially education; this can be seen from the policies of almost all public officials in affected countries who have decided to temporarily close face-to-face educational activities, which ultimately force learning to conducted online, educators in doing online learning generally use familiar applications such as google classroom, zoom, etc. (S. R. Febriani & Anasruddin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Covid-19 pandemic that has attacked the world recently has had a profound impact on all lines of life, especially education; this can be seen from the policies of almost all public officials in affected countries who have decided to temporarily close face-to-face educational activities, which ultimately force learning to conducted online, educators in doing online learning generally use familiar applications such as google classroom, zoom, etc. (S. R. Febriani & Anasruddin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The various assignments can build a process of critical thinking, creative thinking, and students can learn independently in a broader context. And this study found that the impact of technology on students' language skills is when the constructivist approach can provide many opportunities and opportunities for students to be creative through the four Arabic language skills (Febriani & Anasruddin, 2020). Azkia Albantani, in his research entitled Optimizing The Busuu Application In Arabic Learning, states that this website is very relevant to use in foreign language learning, especially Arabic, because this website is supported by a team of native speakers or native speakers from 12 countries (English, French, German, Arabic, Dutch, Italian, Chinese, Japanese, Brazilian, Spanish, Russian and Turkish) and equipped with various learning features, namely; Lessons (Durūs), exercises (Tamārin), Vocabulary (Al-Mufradat) and Personal Notes (Shafhaty al-Syakhsyiah).…”
Section: Introductionmentioning
confidence: 85%
“…Environmental factors have an influence on the language productive abilities of students 27 . Some of these factors can be seen in shabah al-lughah joyful atmosphere which can be seen in Figure 4 below: As language skills cannot be separated from the role of technology 28 . This language environment can be formed through an indoor or outdoor environment 29 .…”
Section: Ma'had Al-jami'ahmentioning
confidence: 99%